An automated multiplex oligonucleotide synthesizer: development of high-throughput, low-cost DNA synthesis. - Lashkari, D A (1995)
An automated oligonucleotide synthesizer has been developed that can simultaneously and rapidly synthesize up to 96 different oligonucleotides in a 96-well microtiter format using phosphoramidite synthesis chemistry. A modified 96-well plate is positioned under reagent valve banks, and appropriate reagents are delivered into individual wells containing the growing oligonucleotide chain, which is bound to a solid support. Each well has a filter bottom that enables the removal of spent reagents while retaining the solid support matrix. A seal design is employed to control synthesis environment and the entire instrument is automated via computer control. Synthesis cycle times for 96 couplings are < 11 min, allowing a plate of 96 20-mers to be synthesized in < 5 hr. Oligonucleotide synthesis quality is comparable to commercial machines, with average coupling efficiencies routinely > 98% across the entire 96-well plate. No significant well-to-well variations in synthesis quality have been observed in > 6000 oligonucleotides synthesized to date. The reduced reagent usage and increased capacity allow the overall synthesis cost to drop by at least a factor of 10. With the development of this instrument, it is now practical and cost-effective to synthesize thousands to tens of thousands of oligonucleotides.